Analysis of the Impact of Reputation and Service Quality on the Saving Interest of the Millennial Generation in Islamic Banks - Risna; Muhammad Ridwan; Jasri (Journal AGENCY, 2026)
This study explores the impact of reputation and service quality on the saving interest of millennial generation at Islamic banks. The main objective is to determine how these factors influence millennials' decision to choose Islamic banks for saving. A quantitative approach was adopted, using a survey method to collect data from 97 respondents in the Pallangga District, Gowa Regency. Data were analyzed using multiple linear regression techniques to assess the relationship between reputation, service quality, and saving interest. The results show that both reputation and service quality significantly influence the saving interest of millennials. Reputation positively affects trust and confidence in Islamic banks, while service quality, including reliability and responsiveness, enhances customer satisfaction, encouraging saving behavior. The study also found that these two factors have a simultaneous effect on millennials' interest in saving at Islamic banks. This research contributes to the understanding of what drives millennial engagement in Islamic banking, emphasizing the importance of reputation and service quality. The findings suggest that Islamic banks should focus on building a positive reputation and enhancing service quality to attract more millennial customers. Future research could explore external factors such as government policies and technological advancements that may also influence millennials' banking preferences.